OTONOMI DAERAH : MASALAH DAN PENYELESAIANNYA DI INDONESIA - Nasution, Akmal Huda (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2016)
The spirit of reform resulted in a new system of governance called regionalautonomy and a regional development strategy as well as the empowerment anddevelopment in accordance with the conditions of Indonesian society is currently inprogress in order to develop democracy in various aspects. This strategy isimplemented as a counter to the economic crisis and the confidence which thenimpact on the change of political power in Indonesia. Regional autonomy and theproblem has been a growing discourse in line with the implementation of regionalautonomy in Indonesia. Regional autonomy is an idea that is ideal for the Republicof Indonesia, but it does not mean that the concept can be implemented simplyflawless and shortcomings. The implementation of regional autonomy and theproblem is still to be studied for academicians and practitioners government,because our country is currently still continue to seek the most appropriate form inthe Indonesian community welfare efforts. The negative impact of the emergence ofregional autonomy is an opportunity for the individuals at the local level for variousoffenses , the appearance of conflict between the central government , and theemergence of the gap between high -income areas Dangan area stillberkembang.Bisa seen that there are still many problems accompany the passageof regional autonomy in Indonesia . The problems that would have sought a solutionand the solution so that the original purpose or noble ideals of autonomy can beachieved and realized will.Keywords: Local autonomy, economic crisis, reform, strategy, counter